The impact of rural industrialization on agriculture in the Taihu area, Jiangsu, China - Gu, Jianming; Gartner, J. A.; Suthad Setboonsarng; Dias, Hiran D.; Japanese Government (Bangkok : Asian Institute of Technology, 1992)
A thesis submitted in partial fulfillment of the requirements for the degree of master of science, School of Environment, Resources and Development
The Taihu area in Jiangsu province was once one of the leading agricultural areas in China . Rural industrialization over the period 1970-1990 changed that position and, as a consequence, the lives of the agricultural population . This study traces the employment and movement of rural labour, examines changes in agricultural production, and evaluates the economy of farm households as rural industrialization passed through its different stages. Surplus rural labour can be absorbed in two ways: increase employment in the agricultural sector or create employment in the non-agricultural sector . In the 1960s and 70s surplus rural labour was absorbed in agricultural production by the intensive exploitation of the land resources in the Taihu area . Expansion of the farming area went hand in hand with the development of multiple-cropping systems and integrated farming systems. During this period rural industry was in the service of agriculture. A change in government policy at the end of the 1970s led to rapid development of rural industry in the Taihu area: the type and scale of industries c hanged as well as the markets they served. Rural labour moved out of agriculture in response to the demand for labour created by industrial development. As a consequence the agriculture sector began to change in order to adapt to the new rural economy . The major movement of labour out of agriculture occurred in the mid - 1980s. This was clearly associated with the rapid development stage in rural industry . In 1991 only one third of farm household labour was engaged in farming activities and the number of labourers in the agricultural sector was less than one person per family. Most of the labour transferred to rural industry within the Taihu area. Some labour moved to other areas and a few obtained employment in urban areas. Agricultural production increased during the early period of industrialization up to 1984 . After t hat it was stagnant and then declined. A decrease in crop production was reflected in the decline of the area used for crops as well as the yield of crops per unit area. The production of commercial agricultural commodities also decreased. The decline in agriculture runs parallel with the loss of labour from t he sector a nd with a reduction in capital input. The economy of farm house holds increased greatly with the advent of employment opportunities in rural industry. More than two thirds of family income came from off- farm employment. Concomitantly, income distribution among farm households improved.
Thesis (M.Sc.) - Asian Institute of Technology, 1992
Keywords: Agriculture and state -- China -- Jiangsu